Developmental biology: holding pattern for histones. - Brasaemle, D.L.; Hansen, J.C. (Current Biology, 2006)
New research on lipid droplets in Drosophila embryos has led to the surprising conclusion that these poorly understood organelles have a novel role as a regulated storage depot of maternally supplied proteins, particularly histones.